Variabilite De La Coloration Du Tegument Des Graines De Voandzou Cultivees Au Burkina Faso Et Les Noms Locaux Associes - Adjima Ouoba; Sabine Nadembega; Moussa N’Golo Konaté; Hervé Nandkangré; Mahama Ouédraogo; Mahamadou Sawadogo (European Scientific Journal, ESJ, 2018)
Vigna subterranea (L.) Verdcourt specie is a traditional African legume, grown in all parts of Burkina Faso. It plays a huge role in the resilience of poor people to food and nutritional insecurity. In order to contribute to the safeguarding of the genetic resources of this specie and to better valorize it in the selection and varietal improvement programs, a study on the phenotypic variability based on the coloration of the seed coat and the nomenclature of the local varieties within certain ethnic groups has been realized. Prospecting and collection of bambara groundnut accessions has made in several localities across the three agro-climatic zones of Burkina Faso. Accessions collected were identified on the basis of seed coat colouring and local names within some ethnic groups. Frequency calculations of the accessions collected according to the staining of tegument were performed. From a total of 138 seed samples collected 322 accessions were obtained with a breakdown into 22 groups of accessions according to the coloration of their tegument. This important phenotypic variability can be exploited in the breeding and varietal breeding programs of bambara groundnut. Knowing the local names of the accessions can also be useful in the nomenclature of the selected varieties and can help in facilitating their adoption by the producers.